TRANSLATION TECHNIQUES OF THE CULTURAL TERMS IN YOGYAKARTA CALENDAR OF EVENTS - Dinar Martia Azizah (Jurnal Bastra (Bahasa dan Sastra), 2025)
The main problems of cultural terms translation is there is not cultural equivalence of the terms form source language into target language because culture of every nation is different. The aim of this research is to describe the types of Yogyakarta cultures and the translation techniques used by the translator in translating the terms in Yogyakarta Calendar of Events. The researcher uses qualitative method to analyze this research. Data source of the research is a Yogyakarta bilingual tourism guide Calendar entitled Yogyakarta Calendar of Event. This bilingual tourism guide Calendar is published by Yogyakarta Tourism Authority. The researcher only selects the words or phrases which that has relation to the Yogyakarta cultural terms and their English translations. The results show that the types of Yogyakarta cultures are traditional ceremony, religious ceremony, traditional attractions, and historical things. In addition, the translation techniques used by the translator in translating Indonesian cultural terms in Yogyakarta Calendar of Events are shift/ transposition, naturalization, transference/ loan word (borrowing), cultural equivalent, literal translation, functional equivalent, reduction, synonymy, modulation, addition. For the future research can be focused on the analysis to measure the quality of accuracy and naturalness of cultural terms translation.